Advancing Safety in the Oil and Gas Infrastructure via Virtual Reality Technology: A Comprehensive Exploration of Hazard Simulation and Visualisations - Muda, Ahmad Syazani; Misnan, Mohamad Farid; Sam, Rosidah; Abdul Aziz, Mohd Azri (International Journal of Integrated Engineering, 2024)
Virtual reality (VR) technology has transformed various industries and technological paradigms, including oil and gas. With so many subareas and techniques in the field, there is a need for organised knowledge about VR applications, particularly in the oil and gas sector. This paper primarily aims to review previous research on virtual reality methods in various industries, including oil and gas. The objective is to offer researchers and professionals valuable insights and provide a foundation for future advancements in VR applications in this sector. A systematic search for publications on "Application of Virtual Reality," "VR," "Advantages of Virtual Reality," and "Immersive Technology in the Oil and Gas Industry Infrastructure" was conducted to understand the field and provide researchers with insights into the VR system. Trusted databases were meticulously explored to facilitate a systematic review process that illuminated publication trends and the origins of the research. This allows civil engineers to model potential dangers on oil and gas platforms, including gas leaks, fires, broken equipment, and structural instability. They also acquire direct experiential knowledge of potential hazards and obstacles by fully immersing themselves in these virtual environments. Additionally, engineers can better visualise potential hazards like trip hazards, obstructions, electrical hazards, or inadequate safety barriers with VR compared to traditional methods. This improves hazard awareness and allows for proactive risk mitigation strategies.